2012
DOI: 10.1177/1538574412442252
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Aneurysmal Repair With Surtureless Visceral Revascularization Using Novel Hybrid Vascular Graft and a Gradual Funneling Technique

Abstract: This article details a novel technique in the treatment of a symptomatic thoracoabdominal aneurysm (TAA) involving the visceral segment and an infrarenal abdominal aortic aneurysm. The patient was treated in a 2-staged hybrid approach combining an endovascular repair of the infrarenal segment, followed by open TAA repair. The large visceral arteries were revascularized using expanded polytetrafluoroethylene GORE Hybrid Vascular Graft (GHVG) and a Gradual Funneling Technique with Dacron graft. This method assur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…There are data suggesting a shortening of renal ischemia and total operative time in open and hybrid repair of TAAA with this graft. 3,26,27 Neither of the 2 patients treated with a 2-staged procedure in the current cohort required postoperative dialysis.…”
Section: Discussionmentioning
confidence: 98%
“…There are data suggesting a shortening of renal ischemia and total operative time in open and hybrid repair of TAAA with this graft. 3,26,27 Neither of the 2 patients treated with a 2-staged procedure in the current cohort required postoperative dialysis.…”
Section: Discussionmentioning
confidence: 98%
“…The device was released in the European market by Gore in 2012 and approved for hemodyalisis access, lower-limb bypass grafting, aortic arch debranching, and visceral revascularization. 15 Bornak et al 16 already report a modified use in a visceral debranching procedure with satisfying early patency.…”
Section: Discussionmentioning
confidence: 99%
“…The device was released by Gore in 2012 in the European market and approved for hemodialysis access, lower limb bypass grafting, aortic arch debranching, and visceral revascularization. 22 Bornak et al 23 reported the first case of sutureless visceral artery revascularization using the GHVG in 2012. They described the treatment of a symptomatic TAAA involving the visceral segment and an infrarenal AAA.…”
Section: Discussionmentioning
confidence: 99%